In situ Fabrication and Photocatalytic Performance of CeO2/Fe2O3 Core-Shell Decorated rGO Nanocomposites - Naidu, K. Satyam (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: This study investigates the in situ fabrication, characterization, and photocatalytic efficiency of CeO2/Fe2O3 core-shell decorated reduced graphene oxide (rGO) nanocomposites for degrading organic pollutants. Materials and Methods: All chemicals were of analytical grade and used without further purification. CeCl3.7H2O and FeSO4.7H2O were dissolved in a 1:1 ratio in 50 mL of double-distilled water, followed by the addition of 0.1 M urea and 0.1 g of as-prepared GO. The solution was ultra-sonicated for 30 min, stirred for 1 h, and then heated at 180°C for 18 h in an autoclave. The precipitate was washed, dried, and calcined at 400°C for 2 h to obtain the CeO2/Fe2O3/r-GO nanocomposite. Photocatalytic activity was tested using 100 mg of the catalyst in 100 mL dye solutions of Indigo Carmine and Eosin Blue (1 × 10−5 M), with pH adjustments. The mixture was stirred for 3 h under visible light from a 200 W tungsten lamp. Dye degradation was monitored by measuring absorbance at 557 nm with a Ultraviolet–visible (UV–Vis) spectrophotometer, and degradation efficiency was calculated. Results and Discussion: The successful synthesis of CeO2/Fe2O3/rGO nanocomposites has shown notable improvements in photocatalytic performance, primarily due to enhanced electron-hole separation and adsorption properties from rGO. Characterizations confirmed efficient charge transfer and reduced recombination rates. UV-Vis spectroscopy and X-ray diffraction validated the nanocomposites’ structural integrity. Photocatalytic tests demonstrated high degradation efficiencies of 86% for Indigo Carmine and 92% for Eosin Blue under sunlight, highlighting their potential for environmental remediation. These results underscore the promise of CeO2/Fe2O3/rGO nanocomposites in sustainable technologies for environmental cleanup and industrial applications. Conclusion: CeO2/Fe2O3/rGO offering an effective and sustainable solution for organic dye degradation in water under visible light irradiation.